Unintended consequences: The impact of Proposition 2½ overrides on school segregation in Massachusetts. - Zabel, Jeffrey. (Tufts University. Tisch Library., 2018)
I investigate a possible unintended consequence of Proposition 2½ override behavior—that it led to increased segregation in school districts in Massachusetts. This can occur because richer, low-minority towns tend to have more successful override votes that attract similar households with relatively high demands for public services who can afford to pay for them. To evaluate this hypothesis, I collect panel data on override behavior from 1982 to 2012 and merge this with data on school district enrollments and other district- and town-level characteristics. I find evidence that passing overrides earmarked for schools results in a significant decrease in the percent of nonwhite students enrolled in Massachusetts school districts. This happens in districts with below-average nonwhite school enrollments, and hence increases segregation. © 2014 Association for Education Finance and Policy.